2020
DOI: 10.1371/journal.pone.0239320
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of anemia among women of reproductive age in Thatta Pakistan: Findings from a cross-sectional study

Abstract: Background Anemia is a major public health concern among women of reproductive age leading to high maternal mortality in low-and middle-income countries. Of the prior studies conducted in Pakistan, most focused on large urban areas and did not explore the determinants of anemia among women of reproductive age (WRA) across socio-demographic, dietary, reproductive, and biological domains. Thus, we aimed to study the prevalence and determinants of anemia among WRA in rural Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…However, the iron deficiency among women of reproductive age was high. The prevalence of iron deficiency was 47% among non-pregnant women of reproductive age and 58% among pregnant women; a similar study from Pakistan showed that 62% of women had a high prevalence of iron deficiency significantly associated with anemia [ 16 ]. This indicates that iron deficiency is common among women of reproductive age in Sudan as a whole and in all the states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the iron deficiency among women of reproductive age was high. The prevalence of iron deficiency was 47% among non-pregnant women of reproductive age and 58% among pregnant women; a similar study from Pakistan showed that 62% of women had a high prevalence of iron deficiency significantly associated with anemia [ 16 ]. This indicates that iron deficiency is common among women of reproductive age in Sudan as a whole and in all the states.…”
Section: Discussionmentioning
confidence: 99%
“…Various determinants of anemia have been recognized in the literature, including inadequate food intake, chronic disease, infections, poverty, high parity pregnancy, and poor access to health services, in addition to genetic and environmental factors [ 16 , 17 , 18 , 19 , 20 ]. The prevalence of all types of anemia among women of reproductive age was high.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia during pregnancy across the world involves around 32 million individuals, approximately 38% of the world population ( Tan et al, 2020 ). According to recent researches 2/3rd of the pregnant population is affected by anemia ( Ali et al, 2020 ). During pregnancy, anemia of mothers could lead to detrimental effects on the newborn ( Sarah et al, 2018 , Shah et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of IDA is declining, still Iron deficiency continues to be the top ranking cause of anemia in children, women and adults worldwide, both in the developed and developing countries 1 . In Pakistan a study from Thatta Sindh, reported 63% prevalence of the Iron deficiency in women in their child gearing age 2 . Iron deficiency (ID) and iron deficiency anemia (I DA) can affect an individual"s emotion, cognition, and development as iron is responsible for many enzymatic activities in the body and is related to development of normal milestone 1 .…”
Section: Introductionmentioning
confidence: 99%